Coordination Cage‐Based Emulsifiers: Templated Formation of Metal Oxide Microcapsules Monitored by In Situ LC‐TEM. Issue 5 (21st December 2021) - Saha, Subhadeep; Chen, Yen‐Ting; Ganta, Sudhakar; Gilles, Markus; Holzapfel, Björn; Lill, Pascal; Rehage, Heinz; Gatsogiannis, Christos; Clever, Guido H.
Abstract: Metallo‐supramolecular self‐assembly has yielded a plethora of discrete nanosystems, many of which show competence in capturing guests and catalyzing chemical reactions. However, the potential of low‐molecular bottom‐up self‐assemblies in the development of structured inorganic materials has rarely been methodically explored so far. Herein, we present a new type of metallo‐supramolecular surfactant with the ability to stabilize non‐aqueous emulsions for a significant period. The molecular design of the surfactant is based on a heteroleptic coordination cage (CGA‐3 ; CGA =Cage‐based Gemini Amphiphile), assembled from two pairs of organic building blocks, grouped around two Pd(II) cations. Shape‐complementarity between the differently functionalized components generates discrete amphiphiles with a tailor‐made polarity profile, able to stabilize non‐aqueous emulsions, such as hexadecane‐in‐DMSO. These emulsions were used as a medium for the synthesis of spherical metal oxide microcapsules (titanium oxide, zirconium oxide, and niobium oxide) from soluble, water‐sensitive alkoxide precursors by allowing a controlled dosage of water to the liquid‐liquid phase boundary. Synthesized materials were analyzed by a combination of electron microscopic techniques. In situ liquid cell transmission electron microscopy (LC‐TEM) was utilized for the first time to visualize the dynamics of the emulsion‐templated formation of hollow inorganic titanium oxide and zirconium oxide microspheres. Abstract : Self‐assembled amphiphiles captured in action : Non‐statistical self‐assembly of heteroleptic coordination cages results in Gemini amphiphiles, able to stabilize non‐aqueous emulsions. Serving as water‐free medium, the emulsion‐templated synthesis of metal oxide microcapsules from water‐sensitive precursors can be carried out in controlled fashion. The formation of hollow metal oxide microcapsules was visualized by in situ liquid cell transmission electron microscopy and elemental mapping.